Peran Strategi Manajemen K3 Dalam Mempersiapkan Mahasiswa Tata Boga Menjadi Tenaga Kerja Kompeten Di Industri Kuliner - Ni Putu Widhya Pibriari; Surya Nugraha (Universitas Triatma Mulya, 2024)
This study aims to explore the role of Occupational Health and Safety (OHS) management strategies in preparing culinary students at the Akademi Komunitas MAPINDO to become competent professionals in the culinary industry. The research focuses on how OHS management strategies are implemented in the culinary education curriculum and their impact on students’ job readiness in the culinary sector. This study employs a mixed-methods approach by combining qualitative and quantitative methods. Qualitative data were collected through in-depth interviews with instructors and culinary industry practitioners to understand the application of OHS strategies in teaching. Quantitative data were obtained through surveys involving culinary students to assess their perceptions of OHS training and its influence on their job readiness. The findings show that the OHS management strategies applied at the Akademi Komunitas MAPINDO significantly contribute to preparing culinary students with the necessary skills to face risks in industrial kitchen environments. Students reported an improved understanding of safety procedures and practical risk-handling skills. Additionally, collaboration between educational institutions and the culinary industry was found to enhance the relevance of the OHS curriculum. This research highlights the importance of OHS management strategies in culinary education, demonstrating that effective integration of OHS into the curriculum can improve students' job readiness and minimize risks in professional kitchen settings. These findings offer valuable insights for curriculum development in culinary education institutions and for safety management practices in the culinary industry.